Conhecimento das precauções padrão e condutas frente a acidentes com material biológico entre funcionários e acadêmicos da Faculdade de Odontologia de Araçatuba - Kato, Mayumi Domingues [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Standard Precautions (SP) are recommendations, among them, the not recapping needles, which purpose is to minimize or prevent the transmission risk of bloodborne pathogens. This study objective was to verify the knowledge and adhesion to the SP, specially the recapping needles practice; the actions to be taken before accidents and related aspects to infection prevention by academics and employees; besides the profile of accidents occured in the Faculdade de Odontologia de Araçatuba (FOA - Unesp). Also observe the location of the sharps disposal containers in the school clinics, the filling conditions and disposed materials. Was applied a semi-structured questionnaire with related questions to 91 senior students from both periods and 21 outsourced cleaning staff from the school. Was also analyzed the information on the Employee's Report of Injury. Between the academics, 79 (86.8%) affirmed the existence of an accident protocol, 82 (90.1%) had received orientation about it and 42 (46.2%) affirmed to know what are the SP. However, 74 (81.3%) affirmed to recap needles, mostly using one hand (78.4%), in order to not let the needle exposed in the table (71.4%). 31 (34.1%) already suffered an accident with biological material, being that 62 (68.1%) did not know the immediate post exposure care, 87 (95.6%) the maximum time to iniciate the HIV post exposure prophylaxy, 78 (85.7%) the duration and 74 (81.3%) the efficiency. 63 (69.2%) did not received an orientation about the Employee's Report Injury. Among the staff, 17 (81%) affirmed the existence of an accident protocol and have received orientation about it; however, 7 (33.3%) did not know the SP. 20 (95.3%) did not know the immediate post exposure care, 18 (85.7%) ignored the maximum time to iniciate the HIV post exposure prophylaxy, 20 (95.3%) the duration and the efficiency. Despite of 9 (42.9%) affirmed to have received orientation about the Employee's Report...

As Precauções Padrão (PP) são recomendações, entre elas o não reencape de agulhas, cuja finalidade é minimizar ou impedir o risco de transmissão de patógenos. O objetivo deste estudo foi verificar o conhecimento e adesão às PP, em especial a prática de não reencapar agulhas; as ações a serem tomadas diante de acidentes e aspectos relativos à prevenção de infecções por acadêmicos e funcionários e o perfil dos acidentes ocorridos na Faculdade de Odontologia de Araçatuba (FOA -Unesp). Além disso, observar a localização dos recipientes de descarte de perfurocortantes nas clínicas da faculdade, as condições de preenchimento e os materiais descartados. Aplicou-se um questionário semiestruturado com perguntas relacionadas ao tema para 91 acadêmicos dos últimos anos dos períodos integral e noturno e 21 funcionários terceirizados da limpeza de uma instituição de ensino superior. Também foram analisadas as informações contidas nas Notificações de Acidente de Trabalho (NATs). Entre os alunos, 79 (86,8%) afirmaram existir um protocolo na faculdade em caso de acidente, 82 (90,1%) disseram ter recebido orientações a respeito e 42 (46,2%) afirmaram saber o que são as PP. Entretanto, 74 (81,3%) afirmaram reencapar agulhas, na maioria dos casos com uma das mãos (78,4%), a fim de não deixar a agulha exposta na bancada (71,4%). 31 (34,1%) já sofreram acidente com material biológico, sendo que 62 (68,1%) não sabiam quais os cuidados imediatos pós-exposição, 87 (95,6%) o prazo máximo para o início da profilaxia pós-exposição ao HIV, 78 (85,7%) a duração e 74 (81,3%) a eficácia. 63 (69,2%) não receberam orientação sobre o preenchimento da NAT. Entre os funcionários, 17 (81%) afirmaram existir um protocolo na faculdade em caso de acidente e terem recebido orientações a respeito; entretanto 7 (33,3%) não sabiam...
Keywords: Estudantes de odontologia; Precauções universais; Biossegurança; Ferimentos penetrantes; Students, Dental